Semantic change in the common Semitic word - shahraa, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
A researcher in the field of Semitic languages finds that there are many words in common amongst these languages as far as pronunciation is concerned. This is what Linguistics idiomatically call ’’ Common Semitic Vocabulary ’’, but the semantic meanings of this vocabulary are different in meaning from what they are in other Semitic languages . It has been clear throughout the research that the meaning of a word is often changed as it moves from one language to another ; its general meaning may be specialized and may limit itself to some of its original language meaning . Its special meaning may be generalized , or it may be used differently from what it is originally used for to from a relation between two meanings . Language is like the living organism and social phenomena . It is subject to the law of evolution and change . There are many other factors which lead to this development . Our main interest in this research is to monitor the semantic changes that can occur in the ’’Common Semitic Vocabulary ’’ . The changes in the semantic meaning of the ’’Common Semitic Vocabulary ’’ that we have observed have motivated us to do this study . We have adopted the comparative approach, which is based on the comparison of the language of one family i.e. Semitic languages family.